Pengaruh Efektivitas Sistem Informasi Akuntansi dengan Budaya Organisasi Sebagai Pemoderasi - Arma Bintang, Dewa Ayu Ari; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2018)
Information technology today is no longer a demand for companies or organizations, but it has become a necessity to demonstrate the work of the company or organization. The role of organizational culture is expected to stimulate employee work discipline, in order to increase employee productivity and work performance so that the goals of a company can be realized. This study aims to determine the effect of the effectiveness of accounting information systems on individual performance with organizational culture as a moderator in the Village Credit Institutions in Tegallalang District. The population in this study amounted to 132 populations. The sample determination method uses saturated sampling technique so that the number of samples is 132 people. Data analysis techniques using Moderating Regression Analysis (MRA) Test. The results of testing the first hypothesis shows that the variable effectiveness of accounting information systems has a positive effect on individual performance. The results of testing the second hypothesis indicate that organizational culture as a moderator is able to strengthen the effect of the effectiveness of the accounting information system on individual performance. Keywords: effectiveness of accounting information systems, organizational culture, individual performanc e.